2016
DOI: 10.1080/10962247.2016.1162227
|View full text |Cite
|
Sign up to set email alerts
|

A biochar-based medium in the biofiltration system: Removal efficiency, microorganism propagation, and the medium penetration modeling

Abstract: Biofiltration is a method of biological treatment belonging to cleaner technologies because it does not produce secondary air pollutants, but helps to integrate natural processes in microorganisms for decomposing volatile air pollutants and solving odor problems. The birch wood biochar has been chosen as a principal material for biofilter bed medium. The experiments were conducted at the temperatures of 24, 28, and 32°C, while the concentration of acetone, xylene, and ammonium reached 300 mg/m 3 and the flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
(23 reference statements)
0
7
0
4
Order By: Relevance
“…The study confirmed that the application of a biofiltration bed containing BC can serve as a carbon source, which not only enhanced the efficiency of biological treatment systems but also enhanced the removal rate of contaminations. Baltrėnas et al (2016) examined the removal of xylene with birch wood BC-based filtration bed and the maximum removal efficiency reached 86%. BC effectively promoted the growth and reproduction of microorganisms, and the colony-forming units reached 10 7 -10 9 CFU/g for fungi, 10 7 -10 10 CFU/g for yeast, and 10 8 -10 10 CFU/g for bacteria, respectively.…”
Section: Biochar-based Biofiltersmentioning
confidence: 99%
“…The study confirmed that the application of a biofiltration bed containing BC can serve as a carbon source, which not only enhanced the efficiency of biological treatment systems but also enhanced the removal rate of contaminations. Baltrėnas et al (2016) examined the removal of xylene with birch wood BC-based filtration bed and the maximum removal efficiency reached 86%. BC effectively promoted the growth and reproduction of microorganisms, and the colony-forming units reached 10 7 -10 9 CFU/g for fungi, 10 7 -10 10 CFU/g for yeast, and 10 8 -10 10 CFU/g for bacteria, respectively.…”
Section: Biochar-based Biofiltersmentioning
confidence: 99%
“…In order to avoid potential drawbacks in BC water system application (e.g., filtering media) and to ensure the durability of BC in biofiltration systems (Baltrėnas et al 2016) or its application in soil (Baltrėnaitė et al 2016) resulting from leaching of DOC, it is fundamental to determine the rate of carbon content that is prone to leaching as DOC and its effect on trace metal speciation and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Per paskutinius kelis dešimtmečius padidėjusios atmosferinių teršalų emisijos tapo viena svarbiausių problemų, su kuria dabartiniame šimtmetyje susiduria pasaulio šalys. Nustatyta, kad oro tarša sukėlė 420 000 priešlaikinių žmonių mirčių Europos Sąjungoje (ES) vien 2010 m. (Baltrėnas et al, 2016). Lakiųjų organinių junginių (LOJ) emisijos sudaro apie 7 % visų atmosferos teršalų, kurių kiekis palaipsniui didėja nuo paskutinio šimtmečio pradžios.…”
Section: Bioanglies Naudojimas Oro Valymo Technologijoseunclassified
“…Morfologinė analizė buvo atlikta naudojantis skenuojančiąja elektronų mikroskopija (SEM) (Baltrėnas et al, 2016). Prieš analizę mėginiai buvo džiovinami 105 °C temperatūroje 24 val., paskui paskirstyti (apytiksliai vienas šaukštas mėginio) ant Petri lėkštelės.…”
Section: Bioanglies Drėkumo Ryšio Su Jos Fizikinėmis Ir Cheminėmis Savybėmis Nustatymasunclassified